Effect of urban structure, population density and proximity to contagion on COVID-19 infections during the SARS-CoV-2 Alpha and Omicron waves in Málaga, Spain, March 2020 to December 2021 - Vargas Molina, Sebastián Alejandro; Sortino-Barrionuevo, Juan Francisco; Perles-Roselló, María Jesús (European Centre for Disease Prevention and Control, 2025)
BackgroundThe potential impact of urban structure, as population density and proximity to essential facilities, on spatial variability of infectious disease cases remains underexplored.AimTo analyse the spatial variation of COVID-19 case intensity in relation to population density and distance from urban facilities (as potential contagion hubs), by comparing Alpha and Omicron wave data representing periods of both enacted and lifted non-pharmaceutical interventions (NPIs) in Málaga.MethodsUsing spatial point pattern analysis, we examined COVID-19 cases in relation to population density, distance from hospitals, health centres, schools, markets, shopping malls, sports centres and nursing homes by non-parametric estimation of relative intensity dependence on these covariates. For statistical significance and effect size, we performed Berman Z1 tests and Areas Under Curves (AUC) for Receiver Operating Characteristic (ROC) curves.ResultsAfter accounting for population density, relative intensity of COVID-19 remained consistent in relation to distance from urban facilities across waves. Although non-parametric estimations of the relative intensity of cases showed fluctuations with distance from facilities, Berman's Z1 tests were significant for health centres only (p < 0.032) when compared with complete spatial randomness. The AUC of ROC curves for population density was above 0.75 and ca 0.6 for all urban facilities.ConclusionResults reflect the difficulty in assessing facilities' effect in propagating infectious disease, particularly in compact cities. Lack of evidence directly linking higher case intensity to proximity to urban facilities shows the need to clarify the role of urban structure and planning in shaping the spatial distribution of epidemics within cities.
Keywords: Pandemia de la COVID-19, 2020-2023; Urban Epidemiology; Public Health Policy; Spatiotemporal Analysis COVID-19; Socioeconomic Disparities; Built Environment